KONSEP SUPERVISI PENDIDIKAN - Meti Fatimah; Salma Navi’ati Kholisa Dewi; Gali Nurma Saudi (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
Educational supervision is a crucial component in efforts to improve the quality of learning and develop teacher professionalism in educational institutions. This study aims to comprehensively examine the concept of educational supervision, encompassing its definition, objectives, functions, principles, types, and the roles of principals and supervisors in its implementation. Using a qualitative method with a literature study approach, data were obtained through analysis of various relevant literature, books, and documents. The study results indicate that educational supervision is not merely administrative oversight, but rather a form of ongoing professional development. Supervision must be conducted with scientific, democratic, cooperative, constructive, practical, objective, and sustainable principles. Types of supervision include academic, administrative, clinical, and individual and group supervision. Principals and supervisors play a strategic role in implementing humanistic and communicative supervision, thereby encouraging teachers to improve their competence and the quality of the learning process and outcomes. Therefore, a proper understanding and implementation of the concept of educational supervision is essential to support the improvement of educational quality in schools.